Tax-Advantaged Trust Use Among IPO Executives: Determinants and Implications for Valuation and Future Performance - Dambra, Michael J.; Gustafson, Matthew; Quinn, Phillip J. (The Accounting Review, 2020)
ABSTRACT We examine the prevalence and determinants of CEOs' use of tax-advantaged trusts prior to their firm's IPO. Twenty-three percent of CEOs use tax-advantaged pre-IPO trusts, and share transfers into tax-advantaged trusts are positively associated with CEO equity wealth, estate taxes, and dynastic preferences. We project that pre-IPO trust use increases CEOs' dynastic wealth by approximately $830,000, on average. We next examine a simple model's prediction that trust use will be positively related to IPO-period stock price appreciation. We find that trust use is associated with 12 percent higher one-year post-IPO returns, but is not significantly related to the IPO's valuation, filing price revision, or underpricing. This evidence is consistent with CEOs' personal finance decisions prior to the IPO containing value-relevant information that is not immediately incorporated into market prices. JEL Classifications: D14; G12; G32; M21; M41. Data Availability: Data are available from the public sources cited in the text.